EpiHRMAssay, in tube and in silico combined approach for the scanning and epityping of heterogeneous DNA methylation. Issue 1 (25th January 2017) - Cirilli, Marco; Delfino, Ines; Caboni, Emilia; Muleo, Rosario
Abstract : Reliable and cost-effective assays with adequate sensitivity are required to detect the DNA methylation profile in plants for scientific and industrial purposes. The proposed novel assay, named EpiHRMAssay, allows to quantify the overall methylation status at target loci and to enable high-throughput analyses. It combines in tube High Resolution Melting Analysis on bisulphite-treated templates with the in silico prediction of the melting profile of virtual epialleles using uMELT SM software. The predicted melting temperatures ( T m-s ) of a set of epialleles characterized by different numbers of methylated cytosines (# m C) or different m C configurations were obtained and used to build calibration models, enabling the quantification of methylation in unknown samples using only the in tube observed melting temperature ( T m-o ). EpiHRMAssay was validated by analysing the promoter region of CMT3, DDM1, and ROS1 genes involved in the regulation of methylation/demethylation processes and chromatin remodelling within a population of peach plants. Results demonstrate that EpiHRMAssay is a sensitive and reliable tool for locus-specific large-scale research and diagnostic contexts of the regulative regions of genes, in a broad range of organisms, including mammals. EpiHRMAssay also provides complementary information for the assessment of heterogeneous methylation and can address an array of biological questions on epigenetic regulation for diversity studies and for large-scale functional genomics.